Assessment of risk of the chemical pollution soil based on solving problems geofiltration - Абрамов, Ігор Борисович; Бойко, Тетяна Владиславівна; Запорожець, Юлія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2012)
The solution of geofiltration task to the region of industrial wastes pumping allows us to construct the velocity field of filtration for the soluble pollutants that are distributed in a layer of soil. Application of the "risk index" allows quantifying the environmental risk